Control of the takeoff phase in one metre springboard forward dives - Sayyah, M.; King, M. A.; Hiley, M. J.; Yeadon, M. R. (XVII International Symposium on Computer Simulation in Biomechanics, July 28th - 30th 2019, Alberta, Canada, 2019)
In springboard diving consistency of body orientation at water entry is necessary for a good dive and is likely to be dependent on the consistency of conditions at takeoff. Elite divers may be expected to be very consistent in the springboard touchdown conditions at the end of the hurdle phase. If open loop control is used the joint angle variability during springboard contact will be solely a function of the variability at touchdown. On the other hand if feedback or feedforward control is used, the joint angle variability will arise mainly from technique adjustments made in each individual dive. Sayyah et al. [1] found that rotation potential at takeoff (angular momentum x flight time) had low variability. The aim of this study was to investigate whether the low rotation potential variability can be attributed to the low variability at touchdown or whether a diver makes configurational adjustments during contact to reduce the rotation variability at takeoff.